(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to explore the origin of Dolohat Weekly Market and its role in Socio-Cultural and Socio-Economic development in Dolohat of Lakhimpur, Assam. Weekly market centers, frequently known as “haats” or “Bazar” play a vital role in the development of Socio-Economic and Socio-Cultural aspects of rural as well as urban communities. The present study investigates the origin, status, and Socio-Cultural relationships between the buyers and sellers of this market centers and their contribution to the overall development of the region. The research employs a mixed-methods approach, including primary and secondary methods of data collection. To gather primary data from the market participants, local authorities, and community members will be taken under consideration. The findings provide valuable insights into the socio-cultural dynamics of the Dolohat weekly market centers and their potential for adopting development in Dolohat of Lakhimpur, Assam.